KALIGRAFI ISLAM DALAM PERSPEKTIF FILSAFAT SENI - Syahrul Kirom; Alif Lukmanul Hakim (UIN Sunan Kalijaga Yogyakarta, 2020)
This article discusses Islamic calligraphy from the perspective of art philosophy. Islamic calligraphy (the art of letter painting) turns out to have values of beauty, uniqueness and spiritual value and has symbolic meaning for Islamic culture. Calligraphy art has religious spiritual meaning and value that causes a person to experience eschatology. Therefore, in this article the author is interested in analyzing Islamic calligraphy with an art philosophy approach. The method used is descriptiveanalytical. This Arabic calligraphy art writer studies by analyzing through its formal object is the philosophy of art. While the material object is to study the meaning of religious-spiritualism which is more philosophical in understanding Islamic calligraphy. The results of this study found that the fact that the art of Islamic calligraphy has beautiful aesthetic values is full of faith and devotion. The existence of Islamic calligraphy art provides meaning and understanding of the process of achieving a very transcendental idea to God.